Skill gaps in nursing and corporate governance challenges - Begum, Anwara (BOHR International Journal of Advances in Management Research, 2024)
Nurses play a vital role in healthcare delivery, yet in South and South Asian countries, particularly during the COVID-19 pandemic, nursing standards have been low and access to quality care has been limited for economically disadvantaged patients. Literature indicates a pressing need for enhanced education and training among nurses, who often lack adequate preparation and, in some cases, a caring approach. In countries like Bangladesh, nursing is perceived as an arduous profession, with its reputation adversely impacted by cultural, religious, and socio-economic factors. This study seeks to explore the challenges faced by economically disadvantaged patients stemming from gaps in nurses’ skills and education, along with the wider implications for patient care. The research employs a mixed-methods approach, combining quantitative analysis of 350 survey responses with qualitative insights drawn from 56 interviews conducted via Google Forms and 30 in-person interviews with patients impacted by COVID-19 and other key stakeholders. Additionally, a quantitative survey of 171 nurses, 32 key informants, and 15 doctors provided further evidence. Findings reveal widespread deficiencies in nursing skills and education, underscoring the need for policy interventions. These insights advocate for focused training initiatives to improve healthcare outcomes for vulnerable populations, including men, women, children, and people with disabilities.